Barakanomic: The Transformation of Modern Muslim Business Ethics - Muhammad Nasir; Rasyidusman Hannamara Furqan Nur; Cut Kumala Sari; Nafisa Suhaila (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
The modernization of Muslim business practices has given rise to a fundamental ethical paradox. On the one hand, Muslims are increasingly involved in modern corporate systems, digitalization, and global trade, but on the other hand, the orientation towards material gain often shifts the spiritual meaning and value of barakah (divine blessing) which is the moral foundation of Islamic economics. This study aims to construct and elaborate on the concept of Barakanomic as an ethical paradigm that reinterprets economic success through the perspective of barakah. Using a conceptual-philosophical approach, this study reviews classical and contemporary literature on Islamic business ethics, the theory of maqāṣid al-syarī‘ah, and critiques of modern capitalism. The results of the study show that Barakanomic offers a transformative ethical framework for modern Muslim businesses by integrating economic rationality and Islamic spirituality. This paradigm emphasizes the importance of moral accountability, social justice, and sustainable welfare that transcends a profit-only orientation. Theoretically, this research contributes to the development of a new ethical model in Islamic economics; practically, Barakanomic can serve as a moral guideline for Muslim entrepreneurs and policymakers in building a fair and blessed economic system.